Melanotic neuroectodermal tumor of infancy: A rare case report - Kulkarni, Tejas; Nagpal, Deepak; Shete, Anagha; Hande, Pratik; Shete, Mrinal (Contemporary clinical dentistry, 2020)
A rare case melanotic neuroectodermal tumor of infancy occurring in 2-year-old girl affecting left maxilla is described. Computed tomography showed benign expansile type of lesion affecting left maxilla. The lesion was surgically excised completely. Histopathology confirmed the diagnosis of melanotic neuroectodermal tumor. Four months' follow-up showed no recurrence.